UTILIZATION OF GAMBIR PLANT (Uncaria gambir) FOR DIRTY WATER TREATMENT - Fadhel Rizky Suryawan; Aulia Aisy Mulyana Pasaribu (CV. Radja Publika, 2025)
Water pollution is one of the major environmental problems currently faced, primarily due to domestic, agricultural, industrial, and mining waste. To address the predicted clean water crisis in 2045, effective, affordable, and environmentally friendly water treatment innovations are needed. This study aims to explore the potential of the gambir plant (Uncaria gambir) as a natural ingredient for purifying dirty water. Gambir is known to contain active compounds such as tannins, flavonoids, and catechins that have coagulant, antibacterial, and adsorbent properties. The research method used a quantitative and experimental approach, with steps such as extracting gambir leaves, treating dirty water, and observing physical changes in the water. The results showed that within two hours, gambir extract was able to significantly reduce the turbidity, odor, and color of dirty water. The addition of natural filters made from betel and lemon strengthened the final results. The conclusion obtained is that the use of gambir for dirty water treatment shows promising effectiveness and is worthy of being developed as an alternative solution for water resource management in the future.